Extracorporeal Membrane Oxygenation in Pregnant and Postpartum Women With H1N1-Related Acute Respiratory Distress Syndrome: A Systematic Review and Meta-analysis. Issue 2 (February 2016) - Saad, Antonio F.; Rahman, Mahbubur; Maybauer, Dirk M.; Fraser, John F.; Costantine, Maged M.; Pacheco, Luis D.; Maybauer, Marc O.
Abstract : OBJECTIVE: To assess available evidence regarding the use of extracorporeal membrane oxygenation (ECMO) in pregnant and postpartum women with acute respiratory distress syndrome (ARDS) secondary to H1N1 infection. DATA SOURCES: Databases from MEDLINE (U.S. National Library of Medicine, 1946 to April 1, 2015), the Cochrane Library Controlled Trials Register, ClinicalTrials.gov, and Web of Science were queried for studies on ECMO in pregnant or postpartum patients with ARDS. Search terms included: "ARDS, " "ECMO, " "pregnant, " and "postpartum." TABULATION, INTEGRATION, AND RESULTS: All relevant references in any language were reviewed. Literature for inclusion and methodologic quality were reviewed based on the meta-analyses and systematic reviews of observational studies (Meta-analysis Of Observational Studies in Epidemiology) guidelines. Of 266 citations, five retrospective studies (39 patients) fulfilled our inclusion criteria. No randomized controlled trials were found. The pooled estimate of the survival rate among pregnant and postpartum patients who received ECMO for ARDS secondary to H1N1 was 74.6% (95% confidence interval [CI] 60.7–88.6%). Neonatal outcomes were reported in two studies and the rate of live birth was 70% (95% CI 43.7–95.2). Heterogeneity was not significant among studies ( I 2 ranged from 0% to 21%; P >.25). CONCLUSION: The role of ECMO in pregnant and postpartum women with ARDS from H1N1 remains unclear and the benefits suggested from our review should be interpreted with caution. Abstract : The role of extracorporeal membrane oxygenation in pregnant and postpartum patients with severe acute respiratory distress syndrome secondary to H1N1 disease remains unclear.